Establishing Credibility for Medical Marijuana: The Proposed Prometheus Dispensary Registry for Botanical Cannabis - Paul Langley (University of Minnesota Libraries Publishing, 2019)
A previous commentary in INNOVATIONS in Pharmacy argued that, given the lack of evidence for outcomes in medical marijuana, outside of a handful of randomized clinical trials and even fewer observational studies, good clinical practice points to the need for monitoring patients who received cannabis through certified medical marijuana dispensaries. The commentary noted the lack of standards for monitoring cannabis patients and the lack of feedback from the dispensary to providers. Botanical cannabis administration was occurring in, effectively, an evidence vacuum. More to the point, dispensary owners and investors seem uninterested in establishing a robust evidence base for cannabis outcomes.  Given the range of conditions and symptoms presented by patients, to include the prevalence of multiple symptoms together with the range of potential cannabis formulations, dosing regimens and delivery options, a failure to monitor patients over the course of their exposure to cannabis in not acceptable. The purpose of this commentary is to report on a proposed on-line registry structure proposed by Prometheus Research for medical marijuana dispensaries in the US. The registry tracks and reports on patients over the course of treatment with botanical cannabis with the focus on severe or chronic non-cancer pain, severe nausea, persistent muscle spasms and seizures, together with prevalent comorbidities - fatigue, anxiety, depression and sleep. This is the first time a registry has been developed for dispensaries in the United States as a model for a robust evidence base to support botanical cannabis as a therapy option.   Article Type: Commentary